Competence assessment in education: research, models and instruments - Leutner, Detlev; Fleischer, Jens; Grünkorn, Juliane; Klieme, Eckhard (Springer, 2017)
1. Competence assessment in education: An introduction -- PART 1: Modeling and assessing student competencies -- 2. Science-P I: Modeling conceptual understanding in primary school -- 3. Science-P II: Modeling scientific reasoning in primary school -- 4. The Heidelberg inventory of geographic system competency model -- 5. An extended model of literary literacy -- 6. Self-regulated learning with expository texts as a competence: Competence structure and competence training -- 7. Investigating pre-service teachers’ professional vision within university-based teacher education -- 8. Teacher knowledge experiment: Conditions for the development of pedagogical content knowledge -- 9. Teachers’ school tracking decisions -- 10. Modeling, measuring, and training teachers´ counseling and diagnostic competences -- 11. Development and evaluation of a competency model for teaching integrative processing of texts and pictures (BiTe) -- PART 3: Modeling and assessing vocational competencies and adult learning -- 12. Multidimensional competency assessments and structures in VET -- 13. Professional competencies of building trade apprentices after their first year of training -- 14. Assessing tomorrow’s potential: A competence measuring approach in vocational education and training -- PART 6: Competency development: Modeling of change and training of competencies -- 15. The development of students’ physics competence in middle school -- 16. Modelling and fostering decision-making competence regarding challenging issues of sustainable development -- 17. Metacognitive knowledge in secondary school students: Assessment, structure, and developmental change -- 18. Development of dynamic usage of strategies for integrating text and picture information in secondary schools -- 19. 20. An intensive longitudinal study on the development of student achievement over two years (LUISE) -- PART 5: Innovations in psychometric models and computer-based assessment -- 21. Multidimensional structures of competencies: Focusing on text comprehension in English as a foreign language -- 22. Multidimensional adaptive measurement of competences -- 23. Development, validation and application of a competence model for mathematical problem solving by using and translating representations of functions -- 24. Relating product data to process data from computer-based competence assessment -- 25. Dynamic problem solving: Multiple-item testing based on minimal complex systems -- PART 6: Feedback from competency assessment: Concepts, conditions and consequences -- 26. Formative assessment in mathematics instruction: Theoretical considerations and empirical results of the Co2CA project -- 27. Arguing validity in educational assessment -- 28. Evaluating prerequisites for the development of a dynamic test of reading competence: Feedback effects on reading comprehension in children.
Keywords: Bildungsprozess; Fachwissen